Non-Candida fungal cholecystitis - an uncommon occurrence even in the right host - Mitchell G. Dumais; Mary M. Czech; Mustafa A. Hyder; Rachel R. Lee; Juan C. Gea-Banacloche; Christopher G. Kanakry; Sun A. Kim; Bindu Adhikari; Matthew D. Surette; Adrian M. Zelazny; Amir Seyedmousavi; Jennifer M. Cuellar-Rodriguez (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Invasive fungal infections (IFI) are a significant cause of morbidity and mortality in hematologic malignancy patients and hematopoietic cell transplant (HCT) recipients. Mold cholecystitis has rarely been described. We present a case of disseminated Lomentospora prolificans , that had recrudescence of symptoms with acute cholecystitis. Treatment included a temporary cholecystostomy and administration of the novel antifungal fosmanogepix. At 6 weeks post-HCT, the patient underwent cholecystectomy and completed a course of fosmanogepix, leading to resolution of her infection. Here we review the published literature on non- Candida fungal cholecystitis, underlying risk factors and treatment.